2005
DOI: 10.1002/apj.5500130513
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemical and Biopulping Process on Bagasse Pulp

Abstract: The amount of sugarcane bagasse in Indonesia is abundant while the utilization is still limited. One of the alternatives f i r bagasse utilization is as pulp material. To minimize the waste from the pulping process, the effect of using a chemical process (with nitric acid) and a biopulping process (using Fusarium solani) were studied and measured by the percentage of a-cellulose content in bagasse pulp. In the chemical process, the nitric acid concentration and the reaction time were varied. llre pulping proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…(Antaresti et al 2005) carried out the study to condense the waste from the pulping process. The effect of using a chemical course (with nitric acid) and a biopulping way (using Fusarium solani) were studied and measured by the percentage of a-cellulose content in bagasse pulp.…”
Section: Environmentalmentioning
confidence: 99%
See 1 more Smart Citation
“…(Antaresti et al 2005) carried out the study to condense the waste from the pulping process. The effect of using a chemical course (with nitric acid) and a biopulping way (using Fusarium solani) were studied and measured by the percentage of a-cellulose content in bagasse pulp.…”
Section: Environmentalmentioning
confidence: 99%
“…The pulping method was conducted at constant temperature of 102°C and the mixture was agitated at 900 rpm (Rodriquez et al 1996). Antaresti et al (2005) reported that the highest percentage of a -cellulose content in pulp was 79.28%, obtained at the concentration of 3.5% for a reaction time of 3.5 h. At higher concentrations and extending considerable cooking times, the a-cellulose decreased due to the cellulose degradation. In the biopulping process, the incubation temperature was kept at 30°C.…”
Section: Environmentalmentioning
confidence: 99%
“…This sugarcane bagasse is favourable in the high-quality green product manufacturing industry due to low production costs 49) . However, utilization of bagasse is still limited but potentially can be converted into useful RE 48), 50) .…”
Section: Other Agriculture Residuesmentioning
confidence: 99%
“…Analysis of decayed sugarcane bagasse by FTIR indicated a correlation between lignin modification and pulp properties in some strains, in such a way that the more the lignin modifies, the more the pulp properties improve (Adilson et al, 1998). Antaresti et al (2008), reported that in the chemical process of bagasse, the nitric acid concentration and the reaction time were varied. The pulping process was conducted at constant temperature of 102 o C and the mixture was agitated at 900 rpm.…”
Section: Unbleached Paper Sheets Of Bagasse As Influenced By Consequementioning
confidence: 99%